PENGARUH KADAR GULA TERHADAP KUALITAS PERMEN JELI BELIMBING WULUH - Merta, Cindy Rahayu; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research was based on the lack of wuluh star fruit utilization, whereas wuluh star fruit has good nutritional value for health. This study aimed to analyzed the effect of sugar content as much as 450 gr, 500 gr, 550 gr and 600 gr to the quality of shape X4 (600 gr), color X4 (600 gr), smell X4 (600 gr), texture X1 (450 gr) and flavor X4 (600 gr) on candy wuluh star fruit. Types of pure experimental research with complete randomized design methods of three repetitions. The research variables included the independent variable (X) that wasthe influence of sugar. The dependent variable (Y) was the quality (shape, color, smell, texture and flavor) candy wuluh star fruit. The data that have been obtained was tabulated and analyzed by variant (ANAVA). If different proceed with Duncan test. Based on the results of the study showed that overall the best value was in the influence of sugar content as much as 600 gr (X4).Keywords: Sugar, Candy Jelly, Wuluh Star fruit, Quality